Uji Organoleptik Telur Asin dengan Berbagai Media Pengasinan - Auliani, Nurul Rizka; Taib, Eva Nauli; Agustina, Elita; Hanim, Nafisah; Zuraidah, Zuraidah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Salted eggs are one from of processed eggs that aims to extend shelf life and improve taste. Biology Education Studentsfrom the 2021 and 2022 classes are khown to only know straw and ash salting media, so this study aims to analyze the effect of four salting media: straw, brunt rice husk, burnt coconut fiber, and salt solution on the organoleptic quality of salted eggs. The research was conducted experimentally using a descriptive analysis approach using averages with 4 treatments and involving 20 panelists from two classes. The parameters tested included aroma, taste, color, and texture using a 5 level Likert scalee. The results of the organoleptic test showed that the burnt rice husk media produced the most preferred taste (score 3.4), the best color was produced by the straw media (score 4), and the highest texture was also found in the burnt rice husk media (score 3.6). The highest aroma was recorded in the straw media (score 3.35). The salt solution media had the lowest scores in almost all aspect. In conclusion, the burnt rice husk media is the most superior media overall in producing preferred salted eggs based on the organoleptic test.